2012
DOI: 10.1007/s10552-012-9900-6
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand smoke exposure at home in rural China

Abstract: Purpose This study estimated secondhand smoke (SHS) exposure at home among nonsmoking children (age 0–18) and adults (age ≥ 19) in rural China, and examined associated socio-demographic factors. Methods A total of 5,442 nonsmokers (including 1,456 children and 3,986 adults) living in six rural areas in China were interviewed in person. The standardized questionnaire obtained information on their demographic characteristics and SHS exposure at home. Differences in SHS exposure were assessed by use of the chi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 14 publications
2
16
0
1
Order By: Relevance
“…A study of SHS exposure in rural areas of China identified that 68% of children were exposed to SHS at home, and that exposure prevalence was further amplified in households with low income or low educational status of the head of household 39 . Prevalence of adult SHS exposure is approximately 35% in Shanghai, but was surprisingly higher in households with children under age 18 years 40 .…”
Section: Epidemiology Of Shs Exposurementioning
confidence: 99%
“…A study of SHS exposure in rural areas of China identified that 68% of children were exposed to SHS at home, and that exposure prevalence was further amplified in households with low income or low educational status of the head of household 39 . Prevalence of adult SHS exposure is approximately 35% in Shanghai, but was surprisingly higher in households with children under age 18 years 40 .…”
Section: Epidemiology Of Shs Exposurementioning
confidence: 99%
“…On the basis of other data obtained by use of biochemical markers this exposure may be even higher among young children who may be highly exposed to tobacco through their parents. The study by Yao et al [26] from rural China reported similar levels of SHS exposure with disparities defined by SEP for children and women. This study emphasizes that SHS exposure is a major contributor to the tobacco epidemic in both urban and rural areas of Eastern Asia.…”
mentioning
confidence: 75%
“…Moreover, lower mean educational level among adults in the household was associated with a greater likelihood that the household would include smokers, a finding that was also found in a study in rural China. 17 One intriguing finding was related to households with intermittent smokers. Households with intermittent smokers (but no daily smokers) had higher economic and educational status than households with no smokers and households with daily smokers.…”
Section: Discussionmentioning
confidence: 99%